2020
DOI: 10.31197/atnaa.752335
|View full text |Cite
|
Sign up to set email alerts
|

Modified Quasi Boundary Value method for inverse source biparabolic

Abstract: In this study, we study an inverse source problem of the bi-parabolic equation. The problem is severely non-well-posed in the sense of Hadamard, the problem is called well-posed if it satisfies three conditions, such as the existence, the uniqueness, and the stability of the solution. If one of the these properties is not satisfied, the problem is called is non well-posed (ill-posed). According to our research experience, the stability properties of the sought solution are most often violated. Therefore, a reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…The number of works on the regularized problem with input data in L 2 is quite abundant. The results of this study can be found in the following documents, attached to the regularization methods: the Tikhonov method, see [14,15], the Fractional Tikhonov method, see [16], the fractional Landweber method, see [17,18], the Quasi Boundary method, see [19], the truncation method, see [20], and their references.…”
Section: Introductionmentioning
confidence: 99%
“…The number of works on the regularized problem with input data in L 2 is quite abundant. The results of this study can be found in the following documents, attached to the regularization methods: the Tikhonov method, see [14,15], the Fractional Tikhonov method, see [16], the fractional Landweber method, see [17,18], the Quasi Boundary method, see [19], the truncation method, see [20], and their references.…”
Section: Introductionmentioning
confidence: 99%
“…The above equation has various applications in areas such as the harmonic oscillator, the damped oscillator and the forced oscillator (see [3]), electrical circuits (see [5]), chaotic systems in dynamics (see [6]), projectile motion (see [7]). Our paper is one of the braches of directions about fractional PDEs, see [15,16,17,18,20].…”
Section: Introductionmentioning
confidence: 99%
“…There are a lot of research results for an inverse source problem of a time-fractional diffusion equation. To do that, during the past decades, a lot of technical developments by mathematicians around the world: Quasi-Reversibility method, see [19], Quasi-Boundary Value method, which readers can see in [20,21], the Landweber iterative method (see [22,23]), the Fractional Landweber method (see [24]), a Tikhonov regularization method (see [25]), a Fourier truncation method (see [26]). However, the object of this topic is to restore the source function F(x) of the problem (1) by the Fractional Tikhonov method.…”
Section: Introductionmentioning
confidence: 99%